2021
DOI: 10.1038/s41598-021-86816-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of intratumoral Fusobacterium nucleatum and association with immune-related gene expression in oral squamous cell carcinoma patients

Abstract: Changes in the oral microbiome, particularly Fusobacterium nucleatum, are associated with oral squamous cell carcinoma (OSCC). F. nucleatum has been reported to modulate local immunity in cancers. We aimed to assess the association between intratumoral F. nucleatum and clinico-pathological features, relapse, and overall survival (OS) in two independent cohorts of patients with OSCC, and to explore the interplay with immune-related genes. We retrospectively analyzed tissue samples from a first cohort of 122 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 43 publications
5
47
1
Order By: Relevance
“…Two recently published studies have examined the prognostic effect of F. nucleatum in oral/head and neck cancer, and the findings are summarised in Table 1 [ 66 , 67 ]. Neuzillet et al found that F. nucleatum was significantly associated with improved overall survival, relapse-free survival and metastasis-free survival in their merged OSCC cohort [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recently published studies have examined the prognostic effect of F. nucleatum in oral/head and neck cancer, and the findings are summarised in Table 1 [ 66 , 67 ]. Neuzillet et al found that F. nucleatum was significantly associated with improved overall survival, relapse-free survival and metastasis-free survival in their merged OSCC cohort [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two recently published studies have examined the prognostic effect of F. nucleatum in oral/head and neck cancer, and the findings are summarised in Table 1 [ 66 , 67 ]. Neuzillet et al found that F. nucleatum was significantly associated with improved overall survival, relapse-free survival and metastasis-free survival in their merged OSCC cohort [ 66 ]. Similarly Chen et al found that F. nucleatum enrichment in HNSCC tumour tissues was significantly associated with better cancer-specific survival and a lower rate of relapse [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial species included in Fusobacterium are significantly enriched in HNSCC tissues, causing increased expression of virulence factors in the oral microbiome [110]. Metaanalysis of patient samples also showed a higher abundance of Fusobacterium in HNSCC tumor samples compared to both adjacent normal tissues and tissues from healthy individuals (Table 1) [110,116,122,123]. Ironically, however, patients with F. nucleatum-positive HNSCC showed a favorable prognosis compared to F. nucleatum-negative HNSCC patients [124], while F. nucleatum in esophageal cancer is associated with aggressive disease and poor survival [117].…”
Section: Differential Contributions Of Oral Microbiome To Hpv+ and Hpv− Hnsccsmentioning
confidence: 99%
“…Ironically, however, patients with F. nucleatum-positive HNSCC showed a favorable prognosis compared to F. nucleatum-negative HNSCC patients [124], while F. nucleatum in esophageal cancer is associated with aggressive disease and poor survival [117]. This may be attributed to F. nucleatum-mediated modulation of local immunity via downregulation of TNFSF4 and PDGFRβ in fibroblasts, both of which are associated with poor prognosis of HNSCC patients [116]. Additionally, F. nucleatum was correlated to low tobacco and alcohol use, suggesting a role in the TME independent of the major risk factors of HNSCC.…”
Section: Differential Contributions Of Oral Microbiome To Hpv+ and Hpv− Hnsccsmentioning
confidence: 99%
“…Additionally, ethanol and its metabolites and the imbalance in the microbiome populations may affect gut permeability, permitting the passage of bacterial metabolites and endotoxins to the general circulation and inducing inflammation both locally and in distant organs [ 15 ]. As a representative example, Fusobacterium nucleatum , a bacteria resident in the oral cavity, secretes immune modulators, virulence factors, and microRNAs linked to the initiation and progression of the oral cavity [ 16 , 17 ], esophagus [ 18 ], or colorectal [ 19 , 20 ] cancer. In biopsies from patients suffering from colorectal cancer, the expanded bacteria population significantly correlated with alcohol consumption [ 20 ].…”
Section: The Route Of Alcohol Through the Gastrointestinal Tract In Humansmentioning
confidence: 99%